FENOMENA BUNUH DIRI TINJAUAN FILSAFAT MANUSIA (Studi Kasus Terhadap Fenomena Bunuh Diri Ibu dan Anak) - Maharani, Septiana Dwiputri (Jurnal Filsafat "WISDOM", 2007)
Suicide in philosophical anthropology is an existential fact of human behavior that individually she has autonomy of her judgment, it has not connection to good and bad ethically and right and wrong religiously. Suicide shows that there are no emphatically attitude of community to human life problems, it views just as an individual problem, so someone will be hopeless if she unable to solve her problems even if it an easy one. Suicide is an alternative and solution for an individual who has no support and emphatically attitude of others (community). Suicide done by a mother and her child is a reflection of complex problems of human life in community that unable to solve by her alone self. A mother has autonomy and responsibility for her child life, so when she judge to ending her life/misery, she has right of her child. The phenomena of suicide of a mother and her child necessarily understood as a â€œlove for childâ€ uniquely.